Maintaining a Balanced Distribution of Language Skills in Textbooks for Young Learners: A Selection of Pedagogical Interventions - Ezzeddine Saidi (Journal of English Language Teaching and Linguistics, 2026)
This study focuses on the importance of maintaining a balanced exposure to the four language skills in English textbooks for Young Learners. Giving equal importance to the four skills in the early stages of language development is crucial to laying a solid foundation for long-term communicative competence. The study uses a mixed-method design to (1) study the distribution of the four language skills in two Tunisian textbooks for young learners, and (2) to propose remedial strategies for teachers to maintain a more equitable skill exposure across the activities presented to learners. The first part is quantitative in nature and reveals a clear imbalance in the teaching of the listening skill, which is completely missing in one textbook and is visibly less frequent in the other. The diagnosed distribution may hinder the attainment of the desired communicative proficiency level declared in the official curriculum and may have longer-term effects on students’ preparation for subsequent learning. To address the uneven distribution of listening skills across the two textbooks, the second part of the study presents a qualitative analysis of selected activities and proposes a range of adaptive solutions that reinforce the integration of listening input into tasks involving the other three language skills, as well as grammar and vocabulary.